ESPACIOS REGIONALES FRONTERIZOS - Meza Monge, Nilo (2010)
If the nation-state has been put in check by process of globalization, what 3could wait about the economic and social processes that operate in border territories where the previous union is reflected with de blur of the imposed limits? In the spaces, there are ways of daily life with independent culture and politic manifestation, giving content to local identities and visions which the Ultra-Nationalists pretended to destroy in the name of the Nation-State. In this text, we will try to understand this process.